DAMPAK KEBIJAKAN DANA DESA (DD) TAHUN 2017 PADA PEMBANGUNAN INFRASTRUKTUR DAN PEMBERDAYAAN MASYARAKAT DI DESA PASSO KOTA AMBON - Hermin Oppier (Jurnal Cita Ekonomika, 2018)
This study aims to find out the impact of the 2017 Village Fund policy on infrastructure development and community empowerment in Passo Village, Ambon City. The Village Fund Policy is determined by the government through Government Regulation No. 60 of 2014 concerning Village Funds sourced from the State Budget and Expenditure. This policy is intended to create a strong, advanced, independent and democratic village so that the role and potential of the village must be empowered. This study uses a qualitative approach with descriptive analysis, the authors will approach the object of research by digging information in accordance with the perceptions of the author and the informant and can develop according to the interactions that occur in the interview process. Data collection techniques used are observation, interviews, documentation. The results of this study state that the Village Fund Program Policy (DD) in Baguala District of Ambon City runs quite well, this can be seen from the Village Fund program activities in accordance with the preparation in the form of a list of proposed activity plans, implementation of each activity, evaluation of activities until the formulation of accountability , and the economy of the people in Baguala Subdistrict increased after the Village Fund program. This is due to the increase in infrastructure in the form of agricultural roads, so that access to transportation from the plantation location is easier, thus accelerating the process of selling agricultural products. Based on the conclusions from the results of the research stated above, suggestions can be given which will be expected to be able to improve or improve the implementation of the Village Fund program in Baguala District, Ambon City in the future.